Fidelity of quantum state transfer of a quantum dot spin qubit - Wufianto, Livardy (2017)
This thesis is written to extend and to improve the previous work in coherent state transfer of singlet-triplet qubit states in linear quantum dots. In this thesis, we investigate the effect of adding rise and fall times of dc voltage pulses to the detuning energy time scale and propose a simple analytic model to further investigate the density matrix elements. In conclusion, the addition of finite rise and fall times of dc voltage pulses lower the fidelity of the state transfer and the longer the rise or fall time is, the lower the fidelity of the state transfer is. While the proposed analytic model and approximate equations give us more insight into the time evolution of density matrix elements. Thus, allowing us to compute better simulation time which increases the fidelity of state transfer by 1.54% to 2% for the case of $0.001 τ.